PERSEPSI SISWA KELAS V SD TERHADAP PEMBELAJARAN DARING DI MASA PANDEMI COVID-19 - Sumarli Sumarli; Nurhayati Nurhayati; Marantika Marantika (STKIP Melawi, 2021)
Abstract: This study aims to describe the perceptions of fifth grade elementary school students towards online learning during the COVID-19 pandemic and the factors that influence it. This study used a qualitative research method. The subjects of this study were 23 students of class V-A SD Negeri 1 Singkawang and 3 students were selected to be interviewed consisting of 1 student with high perception category, 1 student with medium perception category, and 1 student with low perception category. Data collection techniques used student perception questionnaires, interviews, and documentation. The data analysis technique used the Miles and Huberman model, namely data reduction, data presentation, and drawing conclusions. The results showed that students' perceptions on the absorbing indicators that students were able to accept the teaching materials delivered, very easy to interact with fellow students and teachers, and feel comfortable in the learning environment. Students' perceptions on the understanding indicator that students were able to understand the teaching materials that are conveyed and there were also students who understand the lesson only partially, quite easy to interact with fellow students and teachers, and feel comfortable in the learning environment. The factors that supports fifth grade elementary school students in carrying out online learning during the COVID-19 pandemic were that students have facilities to do online learning, such as the availability of mobile phones and textbooks as instructions for students to do assignments. However, the inhibiting factors were network connections that are not smooth, students do not understand how to use media, and students are less enthusiastic about learning.Keywords: Students' Perceptions, Online Learning, The Covid-19 Pandemic Abstrak: Penelitian ini bertujuan untuk mendeskripsikan persepsi siswa kelas V SD terhadap pembelajaran daring di masa pandemi COVID-19 serta faktor-faktor yang mempengaruhinya. Penelitian ini menggunakan metode penelitian kualitatif. Subjek penelitian ini adalah 23 siswa kelas V-A SD Negeri 1 Singkawang dan dipilih 3 siswa untuk diwawancarai yang terdiri dari 1 siswa dengan kategori persepsi tinggi, 1 siswa dengan kategori persepsi sedang, dan 1 siswa dengan kategori persepsi rendah. Teknik pengumpulan data menggunakan angket persepsi siswa, wawancara, dan dokumentasi. Teknik analisis data menggunakan model Miles dan Huberman, yaitu reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa persepsi siswa pada indikator menyerap dikatakan bahwa siswa mampu menerima bahan ajar yang disampaikan, sangat mudah berinteraksi sesama siswa maupun guru, dan merasa nyaman pada lingkungan belajar. Persepsi siswa pada indikator memahami dikatakan bahwa siswa mampu memahami bahan ajar yang di sampaikan dan juga ada siswa yang memahami pelajaran hanya sebagian saja, cukup mudah berinteraksi sesama siswa maupun guru, dan merasa nyaman pada lingkungan belajar. Faktor yang mendukung siswa kelas V SD dalam melaksanakan pembelajaran daring di masa pandemi covid-19 adalah siswa memiliki fasilitas untuk melakukan pembelajaran daring, seperti tersedianya handphone dan buku pelajaran sebagai petunjuk siswa mengerjakan tugas. Namun faktor penghambatnya adalah koneksi jaringan yang kurang lancar, siswa kurang mengerti menggunakan media, dan siswa kurang semangat belajar.Kata Kunci: Persepsi Siswa, Pembelajaran Daring, Pandemi Covid-19